2021
DOI: 10.3390/rs13101887
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Lee Filter Window Size Based on Despeckling Efficiency Prediction for Sentinel SAR Images

Abstract: Radar imaging has many advantages. Meanwhile, SAR images suffer from a noise-like phenomenon called speckle. Many despeckling methods have been proposed to date but there is still no common opinion as to what the best filter is and/or what are its parameters (window or block size, thresholds, etc.). The local statistic Lee filter is one of the most popular and best-known despeckling techniques in radar image processing. Using this filter and Sentinel-1 images as a case study, we show how filter parameters, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Additionally, the resulting extracted water surface masks may be affected by the mixing of multiple pixels near riverbanks. Specifically, the usage of VH polarisation configuration shows wider variability of backscattering in vegetation areas due to volume scattering, confirmed in these publications [77,78].…”
Section: Comparison Of Sar and Multispectral Resultssupporting
confidence: 68%
“…Additionally, the resulting extracted water surface masks may be affected by the mixing of multiple pixels near riverbanks. Specifically, the usage of VH polarisation configuration shows wider variability of backscattering in vegetation areas due to volume scattering, confirmed in these publications [77,78].…”
Section: Comparison Of Sar and Multispectral Resultssupporting
confidence: 68%
“…where Y ∈ R m×n is the target clean image, ζ ∈ R m×n stands for multiplicative noise with assumed variance equal to σ 2 µ , and ⊙ represents point-wise multiplication. The image/noise model relies on general information about SAR image/speckle properties [48].…”
Section: Multi/hyper-spectral Processingmentioning
confidence: 99%
“…One possible way to increase despeckling efficiency is to select optimal parameters for a given filter taking into account image properties and speckle characteristics. Several methods have been proposed for selection of filter parameters [8][9][10]. In [8], adaptive windowing approach has been proposed where the window size is automatically adjusted according to image characteristics (homogeneous or heterogeneous regions) for local statistics Mean and Lee filters.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that it is possible to predict despeckling efficiency beforehand with high accuracy for several filters [12]. We have already demonstrated how to select the window size for the well-known local statistics Lee filter based on despeckling efficiency prediction [10]. Therefore, we demonstrate here that such an approach can be extended to the Frost filter that has two adjustable parameters, with application to real-life Sentinel-1 SAR images in order to provide a better trade-off between speckle suppression and edge/detail preservation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation